Determinants of FDI flows to Sub- Saharan Africa: Does economic development play a role? - Chakufyali, Mukosa (School of Economics, 2024)
There is a disparity in the trends of Foreign Direct Investment (FDI) flows to Sub-Saharan Africa (SSA) across nations at different stages of economic development, thereby indicating that economic development could play a role in attracting FDI to the region. This study assesses whether economic development plays a key role in attracting FDI to SSA, and examines whether the determinants of FDI differs across nations at different stages of economic development. The study constructs a panel dataset consisting of twenty-seven Sub-Saharan African (SSA(n)) nations, separated into higher and lower income nations, for the period 2000- 2019. Both static and dynamic panel regression analysis is conducted, where the dynamic model is estimated using a system of Generalised Method of Moments (GMM) procedure, whereas static panel analysis is conducted using fixed effects and random effects models. A dummy variable is included to represent economic development. The dummy was created by assessing each nations country classification by income level, according to the World Bank, in each year included in the analysis. The study opted against taking a nations classification at the end-point of the analysis, as end-point classification is likely to lead to a misclassification of nations that have transitioned from lower to higher income nations throughout the period under investigation. The full sample regression results found the dummy variable to be strongly significant, thereby supporting the claim that economic development does play a role in attracting FDI to SSA. Additional factors identified to be key drivers of FDI to SSA include inflation, FDI flows in the previous period, and trade openness. A comparison of the determinants of FDI across lower and higher income SSA(n) nations indicates that the determinants of FDI differs across nations at different stages of economic development. The factors that attract FDI to higher income SSA(n) nations are inflation, and government effectiveness, whereas the factors that attract FDI to lower income SSA(n) nations are lagged FDI flows, inflation, and trade openness. Keywords: Determinants of FDI, Panel data analysis, Sub- Saharan Africa. JEL classifications: O11,O4, O43, O57,C33.